2014
DOI: 10.1016/j.talanta.2013.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of rifampicin, clarithromycin and their metabolites in dried blood spots using LC–MS/MS

Abstract: The validated method is applicable for TDM of RIF, CLR and their active metabolites. The stability of the DBS at high temperatures can facilitate the TDM and pharmacokinetic studies of RIF and CLR even in resource limited areas. The role of EDTA and DFX as complexing agents in the extraction was well investigated and may provide a solution for potential applications to other DBS analytical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 27 publications
(53 reference statements)
1
62
0
Order By: Relevance
“…[24] Vu and co-workers thereafter examined the simultaneous determination of rifampicin, clarithromycin, and their metabolites on basis of DBS. [29] Both studies showed promising results for the use of DBS in TDM of anti-TB drugs. A recent review described which drugs used for pulmonary infections were potential candidates for the development and application of DBS monitoring from an analytical and clinical point of view.…”
Section: Dried Blood Spotsmentioning
confidence: 95%
See 2 more Smart Citations
“…[24] Vu and co-workers thereafter examined the simultaneous determination of rifampicin, clarithromycin, and their metabolites on basis of DBS. [29] Both studies showed promising results for the use of DBS in TDM of anti-TB drugs. A recent review described which drugs used for pulmonary infections were potential candidates for the development and application of DBS monitoring from an analytical and clinical point of view.…”
Section: Dried Blood Spotsmentioning
confidence: 95%
“…They also showed that rifampicin was stable for 2 months at ambient temperature. [29] Because DBS improves stability, due to the use of dried blood, it could provide an answer for patients in remote areas where the temperature and humidity are high. Stability of samples under high temperature and humidity is of the utmost importance, because most of the new TB cases in 2014 were diagnosed in Southeast Asia and western Pacific regions (58%) and the African region (29%).…”
Section: Dried Blood Spotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction method for plasma and DBSs was adapted from a previously reported method (19), in which chelation agents were added to prevent RIF binding to ferrous and ferric ions. Plasma was extracted by using a protein precipitation method.…”
Section: Methodsmentioning
confidence: 99%
“…interactions [36,[70][71][72][73]. Voriconazole has a nonlinear pharmacokinetic profile and there is a wide 418 intra and interindividual variety [71].…”
Section: Antifungal Drugs 415mentioning
confidence: 99%